Modification method of high-surface-alkalinity sodium-based active layered oxide positive electrode material
By modifying the sodium-based active layered oxide positive electrode material using weakly protonated organic solvent dispersion of soluble metal salts and sodium sources, the problems of poor material structure instability and cycle stability are solved, and the electrical power of the material is realized Improve chemical performance and surface alkalinity regulation.
Patent Information
- Application Number
- CN202411341941.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-27
AI Technical Summary
The sodium-based active layered oxide positive electrode material has high surface activity, resulting in the formation of residual alkali compounds on the surface and structural instability, affecting the electrochemical performance and cyclic stability.
The high-surface alkaline sodium-based active layered oxide positive electrode material is soaked by weakly protonated organic solvent dispersion of soluble metal salts, filtered and dried, mixed with the sodium source for grinding and sintering to form debasement and structural reconstruction. modified materials.
Effectively remove residual alkaline substances on the surface, avoid structural damage, and improve the structural stability and cyclic stability of the sodium-based active layered oxide positive electrode material.
Smart Images

Figure CN119191385A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of batteries, and in particular to a method for modifying a high-surface alkaline sodium-based active layered oxide positive electrode material. Background Art
[0002] Layered oxide cathode materials are widely used in electrochemical energy storage systems due to their high theoretical specific capacity and low cost. Among them, sodium-based active layered oxides, as emerging cathode materials, have low cost, high theoretical capacity, simple synthesis path and superior electrochemical performance, and are considered to be the material system with the most promising industrial application prospects.
[0003] However, due to its high surface activity, sodium-based active layered oxide positive electrode materials are prone to form a large amount of residual alkaline compounds on the surface after exposure to ambient air, affecting the electrochemical performance and safety; and its wider alkali metal plate layer is prone to slip and produce phase transition when ions are repeatedly inserted / released, thereby accumulating internal stress during the charge and discharge cycle and causing the positive electrode particles to rupture, resulting in structural instability of the sodium-based active layered oxide positive electrode material, which leads to poor cycle stability and reduced cycle stability. Summary of the invention
[0004] The invention discloses a modification method for a sodium-based active layered oxide positive electrode material with high surface alkalinity, which solves the technical problem that the cycle stability of the sodium-based active layered oxide positive electrode material deteriorates due to structural instability during the charge and discharge process.
[0005] In order to solve the above technical problems, the present invention provides a method for modifying a high surface alkalinity sodium-based active layered oxide positive electrode material, comprising the following steps:
[0006] preparing a weakly protonated organic solvent dispersion of a soluble metal salt;
[0007] The high surface alkalinity sodium-based active layered oxide positive electrode material is soaked in the weakly protonated organic solvent dispersion, filtered, and the filtered precipitate is dried to obtain a dealkalized positive electrode material;
[0008] The dealkalized positive electrode material is mixed with a sodium source, ground, and then sintered to obtain a modified sodium-based layered oxide positive electrode material.
[0009] It should be noted that the embodiment of the present invention does not limit the specific source of the high surface alkalinity sodium-based active layered oxide positive electrode material, and it can be prepared according to methods known in the art. For example, the present invention exemplarily provides a method for preparing a high surface alkalinity sodium-based active layered oxide positive electrode material, preferably comprising:
[0010] 50 g of the sodium-based active layered oxide cathode material was placed in a constant temperature and humidity chamber set at 40° C. and 60% RH for 3 days, and then dried in a vacuum drying oven to obtain a sodium-based active layered oxide cathode material with high surface alkalinity.
[0011] It should be noted that the embodiments of the present invention do not limit the parameters in the method, and they can be reasonably selected according to actual conditions.
[0012] In some embodiments, the weakly protonated organic solvent dispersion of the soluble metal salt contains a soluble metal salt at a concentration of 0.5×10 -3 g / mL~5×10 -3 g / mL, preferably 1×10 -3 g / mL.
[0013] In some embodiments, the soluble metal salt may be one of aluminum chloride, aluminum isopropoxide, magnesium chloride, chromium nitrate, and titanium chloride, preferably aluminum chloride.
[0014] It should be noted that the embodiment of the present invention does not limit the form of the soluble metal salt, which can be reasonably selected according to actual conditions. The soluble metal salt can be solid crystals, powder or a dispersion containing a metal salt.
[0015] In some embodiments, the weakly protonated organic solvent is one or more of methanol, ethanol, ethylene glycol, glycerol, acetone, N-methylpyrrolidone, and acetonitrile, preferably ethylene glycol.
[0016] In some embodiments, the sodium source is one of sodium carbonate, sodium oxalate, and sodium citrate, preferably sodium carbonate.
[0017] In some embodiments, the molar ratio of Na in the sodium source to Na in the dealkalized positive electrode material is 1:8-12.
[0018] It should be noted that the molar ratio of Na in the sodium source to Na in the dealkalized positive electrode material can be 1:8, 1:9, 1:10, 1:11, 1:12 or 1:8.5, 1:9.5, 1:10.5, 1:11.5, 1:12.5, etc., any one within the molar ratio range is acceptable, and the embodiment of the present invention is not particularly limited. The molar ratio of Na in the sodium source to Na in the dealkalized positive electrode material is preferably 1:10.
[0019] In some embodiments, the sodium-based active layered oxide cathode material has a structural formula of Na y M α M β Mn x O2 , where M α M is one or more combinations of nickel, cobalt, iron, chromium and vanadium. β It is one or more combinations of lithium, magnesium, potassium, calcium, titanium and niobium, and 0.5≤y≤1, 0≤x≤1.
[0020] In some embodiments, the step of soaking the high surface alkalinity sodium-based active layered oxide positive electrode material in the weakly protonated organic solvent dispersion comprises:
[0021] After the high surface alkalinity sodium-based active layered oxide positive electrode material is dispersed in the organic solvent dispersion by stirring, the dispersion is allowed to stand for 5 minutes to 120 minutes;
[0022] The stirring speed of the stirring and dispersing is 100 rpm to 650 rpm, and the time is 1 min to 120 min;
[0023] And / or, the filtering method is one of normal pressure filtration, suction filtration, and hot filtration;
[0024] And / or, the drying temperature is -20°C to 85°C and the drying time is 10h to 14h.
[0025] It should be noted that the embodiment of the present invention does not limit the drying method, which may be vacuum drying, forced air drying or freeze drying.
[0026] In some embodiments, the sintering temperature is 300° C. to 900° C. and the time is 1 h to 20 h. Preferably, the sintering temperature is 850° C. and the time is 10 h.
[0027] In some embodiments, the milling comprises ball milling;
[0028] The ball milling speed is 200 rpm to 400 rpm, and the time is 2 h to 5 h. The ball milling speed is preferably 300 rpm, and the time is preferably 3 h.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The method provided by the present invention is to soak a sodium-based active layered oxide positive electrode material with a high surface alkalinity in a weakly protonated organic solvent dispersion of a soluble metal salt, and then add a sodium source for mixed grinding and sintering. On the one hand, the weakly protonated organic solvent can be used as a dealkalizing dispersion medium for dissolving residual alkaline substances on the surface, and can effectively dissolve and separate the residual alkaline substances on the surface, and the weakly protonated liquid phase environment provided by the weakly protonated organic solvent can avoid possible structural damage to the sodium-based active layered oxide positive electrode material (such as loss of active sodium, lattice distortion, etc.); on the other hand, the heterogeneous metal ions of the soluble metal salt can construct an alkaline liquid phase complex environment while removing residual alkali on the surface of the sodium-based active layered oxide positive electrode material, forming complex ions enriched on the surface of the material. In the subsequent heat treatment, a sodium source is added for mixed grinding and sintering and curing, so that a reconstructed strengthening layer is formed on its surface, thereby improving the structural stability of the sodium-based active layered oxide positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 This is a graph showing the cycle performance data of the modified sodium-based active layered oxide positive electrode material prepared in Example 2 and Comparative Example 1.
[0033] Figure 2 These are SEM images of the modified sodium-based active layered oxide positive electrode materials prepared in Example 2 and Comparative Example 1. DETAILED DESCRIPTION
[0034] The present invention is described in detail below in conjunction with the accompanying drawings and specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the following examples are conventional means well known to those skilled in the art, and the raw materials, components, etc. used in the following examples, unless otherwise specified, can be obtained from commercial sources.
[0035] In order to illustrate the practical effect of the method of the present invention, the following examples firstly prepare a research model of a high surface alkalinity sodium-based active layered oxide positive electrode material. The preparation method of the model includes:
[0036] 50g NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2The active cathode material was placed in a constant temperature and humidity chamber set at 40°C and 60% RH for 3 days and then dried in a vacuum oven to obtain a high surface alkalinity NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 Model of the cathode material.
[0037] The technical solution of the present invention will be further described below in conjunction with specific embodiments.
[0038] Example 1
[0039] This embodiment provides a method for modifying a high surface alkalinity sodium-based active layered oxide positive electrode material, comprising the following steps:
[0040] 1g aluminum chloride (AlCl 3 ) powder was added into 500 mL of ethylene glycol and stirred for 6 h until completely dissolved to obtain a mixed solution.
[0041] Take 10g of high surface alkalinity NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 The positive electrode material was added to the mixed solution to obtain a solid-liquid mixed phase. The solid-liquid mixed phase was magnetically stirred at 550 rpm for 5 min until it was uniformly dispersed. The mixture was suction filtered using slow quantitative filter paper and dried in a vacuum drying oven set at 80°C for 12 h to obtain the dealkalized positive electrode material.
[0042] 1.9 g of anhydrous sodium carbonate powder (10% relative to the molar amount of Na in the positive electrode material) was added to the dealkalized positive electrode material and ball-milled in a planetary ball mill at 300 rpm for 3 h to obtain a mixed powder.
[0043] The mixed powder was placed in a muffle furnace for sintering treatment, the temperature was increased to 850°C at a heating rate of 5°C / min and kept warm for 10 hours, and naturally cooled to room temperature to obtain a modified sodium-based active layered oxide positive electrode material I (product).
[0044] Example 2
[0045] This embodiment provides a method for modifying a high surface alkalinity sodium-based active layered oxide positive electrode material, comprising the following steps:
[0046] 0.5 g aluminum chloride (AlCl 3 ) powder was added into 500 mL of ethylene glycol and stirred for 6 h until completely dissolved to obtain a mixed solution.
[0047] Take 10g of high surface alkalinity NaNi 1 / 3 Fe1 / 3 Mn 1 / 3 O 2 The positive electrode material was added to the mixed solution to obtain a solid-liquid mixed phase. The solid-liquid mixed phase was magnetically stirred at a rotation speed of 550 rpm for 5 minutes until it was evenly dispersed, and was allowed to stand for 1 hour. It was suction filtered using slow quantitative filter paper and dried in a vacuum drying oven set at 80°C for 12 hours to obtain the dealkalized positive electrode material.
[0048] 1.9 g of anhydrous sodium carbonate powder (10% relative to the molar amount of Na in the positive electrode material) was added to the dealkalized positive electrode material and ball-milled in a planetary ball mill at 300 rpm for 3 h to obtain a mixed powder.
[0049] The mixed powder was placed in a muffle furnace for sintering treatment, the temperature was increased to 850°C at a heating rate of 5°C / min and kept warm for 10 hours, and naturally cooled to room temperature to obtain a modified sodium-based active layered oxide positive electrode material II (product).
[0050] Comparative Example 1
[0051] This comparative example is a high surface alkalinity NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 Positive electrode material.
[0052] Comparative Example 2
[0053] This comparative example provides a method for dealkalization of a high surface alkalinity sodium-based active layered oxide positive electrode material, comprising the following steps:
[0054] Take 10g of high surface alkalinity NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 The positive electrode material was added to 500 mL of ethylene glycol to obtain a solid-liquid mixed phase. The solid-liquid mixed phase was magnetically stirred at a rotation speed of 550 rpm for 5 min until it was uniformly dispersed. The mixture was suction filtered using a slow quantitative filter paper and dried in a vacuum drying oven set at 80° C. for 12 h to obtain a sodium-based active layered oxide positive electrode material III (product).
[0055] Comparative Example 3
[0056] This comparative example provides a method for dealkalization of a high surface alkalinity sodium-based active layered oxide positive electrode material, comprising the following steps:
[0057] Take 10g of high surface alkalinity NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2The positive electrode material was added to 500 mL of ethylene glycol to obtain a solid-liquid mixed phase. The solid-liquid mixed phase was magnetically stirred at 550 rpm for 5 min until it was uniformly dispersed. The mixture was suction filtered using slow quantitative filter paper and dried in a vacuum drying oven set at 80° C. for 12 h to obtain the dealkalized positive electrode material (product).
[0058] The dealkalized positive electrode material was placed in a muffle furnace for sintering treatment, heated to 850°C at a heating rate of 5°C / min and kept warm for 10 hours, and naturally cooled to room temperature to obtain a sodium-based active layered oxide positive electrode material IV (product).
[0059] Experimental Example 1
[0060] This experimental example provides an electrochemical performance test experiment for sodium-based active layered oxide positive electrode materials.
[0061] 400 mg of the material to be tested, 50 mg of polyvinylidenefluoride (PVDF) and 50 mg of conductive carbon black were prepared into a slurry in N-methylpyrrolidone (NMP), coated on an aluminum foil with a scraper at a height of 250 μm, and dried to form a positive electrode sheet, which was punched into a sheet with a diameter of 12 mm to obtain a positive electrode sheet. The obtained positive electrode sheet was used as the positive electrode and assembled into a button cell with a sodium metal negative electrode.
[0062] The products prepared in Examples 1-2 and Comparative Examples 1-3 were respectively used as test materials to assemble button batteries, and the electrochemical performance tests were performed. The results are shown in Table 1. The products prepared in Example 2 and Comparative Example 1 were respectively used as test materials to assemble button batteries, and the cycle performance results are shown in Table 1. Figure 1 shown.
[0063] Table 1 Electrochemical performance test results
[0064]
[0065] From Table 1 and Figure 1It can be seen that due to the weak conductivity of the high surface residual alkali and the loss of sodium in the material, the discharge specific capacity of Comparative Example 1 is significantly reduced, and the capacity retention rate after cycling is low. After the residual alkali is cleaned in Comparative Example 2, partial capacity recovery and stability improvement occur. After the residual alkali is removed and sintered in Comparative Example 3, the capacity is further recovered and the cycle stability is greatly improved, which shows that sintering has an important influence on the repair of the positive electrode material structure. Examples 1-2 introduced metal complex ions into the weakly protonated organic solvent and constructed a surface strengthening layer. Examples 1-2 both showed a significant improvement in the discharge specific capacity. The discharge specific capacity and capacity retention rate after cycling of Example 1 are slightly lower, which is attributed to the fact that the introduction of more metal ions affects the electrochemical reaction activity on the surface of the positive electrode material. The first cycle discharge specific capacity of Example 2 was restored to 120.11mAh / g and still retained 86.7% of the discharge specific capacity after 1C and 200 cycles. It is illustrated that the method provided by the present invention achieves the comprehensive goal of enhancing the structural reconstruction and regulating the surface alkalinity of the sodium-based active layered oxide positive electrode material, thereby improving the cycle stability of the sodium-based active layered oxide positive electrode material.
[0066] Experimental Example 2
[0067] This experimental example provides a scanning electron microscope (SEM) test experiment of a sodium-based active layered oxide positive electrode material.
[0068] The samples to be tested are tested using a scanning electron microscope. All tests are conducted in an atmospheric environment.
[0069] The sodium-based active layered oxide positive electrode material II prepared in Example 2 and the high surface alkalinity NaNi prepared in Comparative Example 1 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 The positive electrode materials were tested as samples, and the results were as follows: Figure 2 shown.
[0070] Depend on Figure 2 It can be seen that the high surface alkalinity NaNi prepared in Comparative Example 1 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 The surface of the positive electrode material is covered with residual alkaline substances, while the surface of the sodium-based active layered oxide positive electrode material II prepared in Example 2 has basically no residual alkaline substances, which shows that the residual alkaline substances covering the surface of the sodium-based active layered oxide positive electrode material III can be basically removed by the method of the present invention, and after a reconstruction strengthening layer is formed on its surface, a relatively clean surface and particle contour are exhibited, thereby improving the structural stability of the sodium-based active layered oxide positive electrode material.
[0071] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0072] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for modifying a high surface alkalinity sodium-based active layered oxide positive electrode material, characterized in that: The following steps are involved: preparing a weakly protonated organic solvent dispersion of a soluble metal salt; The high surface alkalinity sodium-based active layered oxide positive electrode material is soaked in the weakly protonated organic solvent dispersion, filtered, and the filtered precipitate is dried to obtain a dealkalized positive electrode material; The dealkalized positive electrode material is mixed with a sodium source, ground, and then sintered to obtain a modified sodium-based layered oxide positive electrode material.
2. The method for modifying the high surface alkalinity sodium-based active layered oxide positive electrode material according to claim 1, characterized in that: The weakly protonated organic solvent dispersion of the soluble metal salt contains a soluble metal salt at a concentration of 0.5×10 -3 g / mL~5×10 -3 g / mL.
3. The method for modifying the high surface alkalinity sodium-based active layered oxide positive electrode material according to claim 1, characterized in that: The soluble metal salt may be one of aluminum chloride, aluminum isopropoxide, magnesium chloride, chromium nitrate, and titanium chloride.
4. The method for modifying the high surface alkalinity sodium-based active layered oxide positive electrode material according to claim 1, characterized in that: The weakly protonated organic solvent is any one or more of methanol, ethanol, ethylene glycol, glycerol, acetone, N-methylpyrrolidone and acetonitrile.
5. The method for modifying the high surface alkalinity sodium-based active layered oxide positive electrode material according to claim 1, characterized in that: The sodium source is one of sodium carbonate, sodium oxalate and sodium citrate.
6. The method for modifying the high surface alkalinity sodium-based active layered oxide positive electrode material according to claim 5, characterized in that: The molar ratio of Na in the sodium source to Na in the dealkalized positive electrode material is 1:8-12.
7. The method for modifying a high surface alkalinity sodium-based active layered oxide positive electrode material according to claim 1, characterized in that: The structural formula of the sodium-based active layered oxide positive electrode material is Na y M α M β Mn x O2, where M α M is one or more combinations of nickel, cobalt, iron, chromium and vanadium. β It is one or more combinations of lithium, magnesium, potassium, calcium, titanium and niobium, and 0.5≤y≤1, 0≤x≤1.
8. The method for modifying a high surface alkalinity sodium-based active layered oxide positive electrode material according to claim 1, characterized in that: The step of soaking the high surface alkalinity sodium-based active layered oxide positive electrode material in the weakly protonated organic solvent dispersion comprises: After the high surface alkalinity sodium-based active layered oxide positive electrode material is dispersed in the organic solvent dispersion by stirring, the dispersion is allowed to stand for 5 to 120 minutes; The stirring speed of the stirring and dispersing is 100 rpm to 650 rpm, and the time is 1 min to 120 min; And / or, the filtering method is one of normal pressure filtration, suction filtration, and hot filtration; And / or, the drying temperature is -20°C to 85°C and the drying time is 10h to 14h.
9. The method for modifying a high surface alkalinity sodium-based active layered oxide positive electrode material according to claim 1, characterized in that: The sintering treatment is performed at a temperature of 300° C. to 900° C. and for a time of 1 h to 20 h.
10. The method for modifying the high surface alkalinity sodium-based active layered oxide positive electrode material according to claim 9, characterized in that: The grinding comprises ball milling; The ball milling speed is 200 rpm to 400 rpm, and the time is 2 h to 5 h.
